THE OTHER IS DEAD - Attila KOVÁCS (Studia Universitatis Babeș-Bolyai. Philosophia)
The question is whether we can even speak about alterity in our current world, whether the meeting of the other is possible at all, and if it is, whether it should be discussed in an ontical-ontological, an ethical (Lévinas), or a social (Baudrillard) framework. In the ecstasy of communication (Baudrillard), the Other appears not as an autonomous person carrying an existential message, but as one of the elements of the system bridging the gap between the communicating parties. As soon as the world becomes a transparent network, the Other loses his transcendent character and is reduced to an insignificant hub in the network that unites the world. We cannot speak of authentic alterity in such a network-like world, as otherness has become an element within an arbitrarily shaped electronic system. An authentic Other is not even possible, since alterity can always be arbitrarily modeled with the necessary technological instruments in the playing field of production. Hence, the Nietzschean dictum God is dead receives a new interpretation in this context.